Beckman Facilities, England (1985)
The black and white photograph is dated to 1985. The color photograph bears an illegible photographer's stamp and is identified as Beckman RIIC Ltd. Sales and Service Operation.
Keywords: Buildings; Beckman Instruments, Inc.